MUTHLAQ DAN MUQAYYAD SEBAGAI METODE ISTINBAT HUKUM DARI ALQURAN DAN HADIS - Enny Nazrah Pulungan (Universitas Islam Negeri Sumatera Utara Medan, 2019)
Ushuliyah rules are rules relating to language. And ushuliyah rules are also very important rules, because the ushuliyah rule is a medium or tool to explore the contents of meaning and law that contained in the Quran and Sunnah, the ushuliyah rule is also called by the istinbath rule or the lughawiyah rule. Among several discussions relating to the ushuliyah rule are muthlaq and muqayyad Muthlaq is a lafazh (pronunciation) which has no limits or no ties to other words, for example a school teacher or textbooks. The range of understanding of the lafazh has been limited or narrower when compared to the other lafazh, each of these lafazh after being associated with other lafazh is called by Muqayyad